2019
DOI: 10.1186/s12935-019-0817-y
|View full text |Cite
|
Sign up to set email alerts
|

Construction and comprehensive analysis of a ceRNA network to reveal potential prognostic biomarkers for hepatocellular carcinoma

Abstract: Background: Long noncoding RNAs (lncRNAs) can act as microRNA (miRNA) sponges to regulate protein-coding gene expression; therefore, lncRNAs are considered a major part of the competitive endogenous RNA (ceRNA) network and have attracted growing attention. The present study explored the regulatory mechanisms and functional roles of lncRNAs as ceRNAs in hepatocellular carcinoma (HCC) and their potential impact on HCC patient prognosis. Methods: In this study, we systematically studied the expression profiles an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 64 publications
1
82
0
Order By: Relevance
“…MiRNAs, included in ncRNAs, are identified to be evolutionarily conserved, with an average length of 22-nt, and may bind to the 3'untranslated region (3'UTR) of the targeted mRNAs according to the principle of complementary base pairing. An increasing body of evidence has demonstrated that dysregulated miRNAs play a crucial role in the initiation, progression, and therapy of various tumors [4,28,34]. Baolei et al revealed that miRNA-124 is a negative regulator of HCC with respect to proliferation and invasion by downregulating lncRNA-UCA1 [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MiRNAs, included in ncRNAs, are identified to be evolutionarily conserved, with an average length of 22-nt, and may bind to the 3'untranslated region (3'UTR) of the targeted mRNAs according to the principle of complementary base pairing. An increasing body of evidence has demonstrated that dysregulated miRNAs play a crucial role in the initiation, progression, and therapy of various tumors [4,28,34]. Baolei et al revealed that miRNA-124 is a negative regulator of HCC with respect to proliferation and invasion by downregulating lncRNA-UCA1 [35].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most universally malignant tumors in the world, with increasing morbidity and mortality [1,2]. Currently, it is the fifth most common cancer and the fourth leading cause of cancer-related death worldwide [3,4]. Tumorigenesis of HCC is correlated with several liver primary diseases, such as viral infections, including Hepatitis B virus (HBV), Hepatitis C virus (HCV), and other kinds of hepatotropic viruses, as well as alcoholic liver diseases, dietary aflatoxin exposure diabetes, and other diseases [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By sponging microRNAs, lncRNAs revealed many significant instances of their influence on post-transcriptional regulation in a variety of cancers [41,42]. Their influence is controlled through mechanisms like the competitive endogenous model (ceRNA) [43] which will ultimately affect gene expression based on the binding activity of microRNAs. Despite established investigations of miRNA and lncRNA interactions, lncRNA-RBP binding activity is not well explored in a context of post-transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA NEAT1 contributes to lung cancer cell proliferation and invasion via NEAT1/miR-1224/KLF3 ceRNA pattern [10].Long intergenic non-coding RNA 00221 (LINC00221) was reported to enhance the cisplatin resistance of non-small cell lung cancer [11]. Also, LINC00221 is a prognostic biomarker for patients with hepatocellular carcinoma [12]. Besides, GEPIA database (http://gepia.cancer-pku.cn/) indicated that LINC00221 was conspicuously down-regulated in acute myeloid leukemia.…”
mentioning
confidence: 99%